PKM kelompok Guru SMKN 4 Pinrang dalam melaksanakan Penelitian Tindakan Kelas - Army Auliah; Ramdani Ramdani; Darminto Darminto (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
Workshops and mentoring planning for Classroom Action Research (CAR) have been conducted. This activity, which is a community partnership program, was carried out in Tonyamang village, Patampanua sub-district, Pinrang Regency, involving 27 teachers of 4 Pinrang Vocational Schools. The results of the activity showed that the enthusiasm of the teacher was so great in attending the workshop. They have also succeeded in making a CAR draft which will be applied to each teacher's class.